Experimental development and optimization of a standing wave thermoacoustic refrigerator using additive manufactured stacks. (February 2023) - Sarpero, Emanuele; Gourdon, Emmanuel; Borelli, Davide
Highlights: Multi-objective optimization of a standing wave thermoacoustic refrigerator. Additive manufacturing of stacks for thermoacoustic refrigeration. Thermophysical characterization of the 3D printing material used for the stacks. Abstract: While many previous research publications focused on developing simple and inexpensive acoustic refrigerator prototypes, the current state of play in the field reveals the need to elaborate robust and replicable facilities for experimental and test purposes. In this context, the present article justifies the importance of an economical and technologically simple process demonstrator. The construction of an experimental Thermo-Acoustic Refrigerator (TAR), employing an acoustic-to-thermal energy conversion cycle, is further described. Setup's repeatability and replicability and results' robustness were primarily addressed, while innovative techniques for stack production and optimization were also proposed. The success of experiments in terms of optimization and reproducibility was validated via the temperature gradients obtained. The adequacy of experimental results was verified by comparing them with a numerical simulation using the DeltaEC software.